Enhancing Vocational Students’ Competencies through Dialogflow-Based Chatbot Training with Consistent Communication Style for Digital Branding - Suyahman Suyahman; Ardy Wicaksono; Yulaikha Mar'atullatifah (Jurnal Pengabdian IPTEK, 2026)
The rapid adoption of artificial intelligence in digital services has increased the relevance of chatbot technology in customer service and digital branding contexts. However, vocational students often receive training that emphasizes technical functionality without sufficient attention to communication consistency and branding strategy. This community engagement program aimed to enhance vocational students’ competencies by integrating Dialogflow-based chatbot development with consistent communication style design to support digital branding. The program employed a practice-oriented training approach consisting of conceptual instruction, hands-on development, and reflective evaluation, involving vocational high school students as participants. The results indicate that participants demonstrated improved understanding of chatbot concepts, acquired foundational technical skills in Dialogflow, and developed greater awareness of communication consistency and brand voice in chatbot interactions. The integration of technical and communicative aspects contributed to more coherent and user-oriented chatbot designs. These findings suggest that community-based training models combining applied artificial intelligence and digital communication strategy can effectively support holistic competency development in vocational education and strengthen students’ readiness for contemporary digital service environments.